Crime, conflict, and fighting for fun: types of juvenile homicide offenders in Australia - Deegan, Simone (The Routledge international handbook of juvenile homicide, 2024)
In this chapter, I offer the first snapshot of youth homicide offending in (South) Australia and explore the themes running through four specific scenarios of lethal violence: confrontational homicide, homicide in the course of other crime, conflict-resolution homicide, and revenge homicide. I draw on selected narratives of every young person currently serving life imprisonment for murder in South Australia to build a picture of their primary purpose for being at the scene and interacting with the victim. Second, I comment on the social, cultural, familial, and economic conditions that frame young homicide offenders’ lives and which, at critical moments in time, have likely underscored events that led to the killing. I conclude with the claim that for the majority of young people, it was not part of the original plan to kill the victim. I then consider what these events suggest for how we might prevent such occurrences in the future.